Removal of Pb2+ from Water Using Sustainable Brown Seaweed Phlorotannins - Zhang, Rui; Richardson, Joseph J; Masters, Anthony F; Maschmeyer, Thomas (Langmuir, 2022)
Bioadsorption is a promising technology to sequester heavy metal ions from water, and brown seaweed has been identified as one of the most appropriate adsorbents as it is abundant, low cost, and efficient at removing various metal ion contaminations. The ability to remove heavy metals from water arises from the high concentration of polysaccharides and phlorotannins in brown seaweed; however, remediation can be hampered by the salinity, location, and coexistence of pollutants in the contaminated water. Maintaining the adsorbent properties of brown seaweed while avoiding the fragility of living organisms could allow for the development of better adsorbents. Herein, we demonstrate that polymerized phlorotannin particles, synthesized from phlorotannins extracted from a species of brown seaweed (Carpophyllum flexuosum), were able to remove 460 mg of Pb2+ from water per gram of adsorbent. Scanning electron microscopy (SEM), attenuated total reflectance Fourier-transform infrared spectroscopy (ATR-FTIR), and thermogravimetric analysis (TGA) were used to characterize the polymerization process and the polymerized phlorotannin particles. Importantly, there was no direct correlation between the Pb2+ removal capacity and the phlorotannin content of various algal derivatives of three species of brown seaweed, C. flexuosum, Carpophyllum plumosum, and Ecklonia radiata, as all three had similar adsorption capacities despite differences in phlorotannin content. This work shows that naturally abundant, "green" materials can be used to help remediate the environment.Bioadsorption is a promising technology to sequester heavy metal ions from water, and brown seaweed has been identified as one of the most appropriate adsorbents as it is abundant, low cost, and efficient at removing various metal ion contaminations. The ability to remove heavy metals from water arises from the high concentration of polysaccharides and phlorotannins in brown seaweed; however, remediation can be hampered by the salinity, location, and coexistence of pollutants in the contaminated water. Maintaining the adsorbent properties of brown seaweed while avoiding the fragility of living organisms could allow for the development of better adsorbents. Herein, we demonstrate that polymerized phlorotannin particles, synthesized from phlorotannins extracted from a species of brown seaweed (Carpophyllum flexuosum), were able to remove 460 mg of Pb2+ from water per gram of adsorbent. Scanning electron microscopy (SEM), attenuated total reflectance Fourier-transform infrared spectroscopy (ATR-FTIR), and thermogravimetric analysis (TGA) were used to characterize the polymerization process and the polymerized phlorotannin particles. Importantly, there was no direct correlation between the Pb2+ removal capacity and the phlorotannin content of various algal derivatives of three species of brown seaweed, C. flexuosum, Carpophyllum plumosum, and Ecklonia radiata, as all three had similar adsorption capacities despite differences in phlorotannin content. This work shows that naturally abundant, "green" materials can be used to help remediate the environment.